Mitigating the Effects of Salinity by Foliar Application of Salicylic Acid in Fenugreek. (1st April 2014) - Babar, Sumaira; Siddiqi, Ejaz Hussain; Hussain, Iqbal; Hayat Bhatti, Khizar; Rasheed, Rizwan
Abstract : Present research work was conducted to alleviate the salinity-induced harmful effect on biomass production and physiochemical attributes of fenugreek by foliar application of salicylic acid. Two varieties (Deli Kabul and Kasuri) were grown in salt treated (100 mM NaCl) and untreated (0 mM NaCl) growth medium. Two levels of salicylic acid (0 mg L −1 and 100 mg L −1 ) were applied through foliar method. Salinity stress significantly reduced the growth biomass in both varieties. Higher shoot fresh weight was recorded in Deli Kabul, while lower in Kasuri. Such reduction in growth biomass was mitigated by the foliar application of SA in both plants. Salinity caused a marked reduction in gas exchange attributes including net CO2 assimilation rate, transpiration rate, stomatal conductance, and substomatal CO2 concentration. Exogenous applied salicylic acid also overcomes the reduction in gas exchange attributes of the plants. The varieties "Deli Kabul" and "Kasuri" showed higher and lower net CO2 assimilation rate, respectively. These results indicate that growth medium salinity induced reduction in biomass production, gas exchange attributes, and also chlorophyll contents whereas the application of SA through foliar method can be used to protect plant growth and improve these attributes under salt stress.